2018
DOI: 10.1038/s41386-018-0300-9
|View full text |Cite
|
Sign up to set email alerts
|

T-448, a specific inhibitor of LSD1 enzyme activity, improves learning function without causing thrombocytopenia in mice

Abstract: Dysregulation of histone H3 lysine 4 (H3K4) methylation has been implicated in the pathogenesis of several neurodevelopmental disorders. Targeting lysine-specific demethylase 1 (LSD1), an H3K4 demethylase, is therefore a promising approach to treat these disorders. However, LSD1 forms complexes with cofactors including growth factor independent 1B (GFI1B), a critical regulator of hematopoietic differentiation. Known tranylcypromine-based irreversible LSD1 inhibitors bind to coenzyme flavin adenine dinucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 45 publications
(60 reference statements)
0
45
0
Order By: Relevance
“…S1, A to D, and table S1). We have previously found that LSD1 inhibition could increase histone methylation at Ucp2 and Bdnf genes ( 13 ). Thus, histone methylation levels of these genes were used as markers for LSD1 inhibition by TAK-418.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1, A to D, and table S1). We have previously found that LSD1 inhibition could increase histone methylation at Ucp2 and Bdnf genes ( 13 ). Thus, histone methylation levels of these genes were used as markers for LSD1 inhibition by TAK-418.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on LSD1, which demethylates mono- and dimethylated H3K4 (H3K4me1/2) and histone H3 lysine 9 (H3K9me1/2) ( 10 , 11 ). LSD1 has been considered to regulate gene expression through two functions: histone demethylation and scaffolding activity for cofactors, including growth factor independent 1B (GFI1B), a critical regulator of hematopoietic differentiation ( 12 , 13 ). In the previous study, characterization of two LSD1 inhibitors [ N -(4-( trans -2-((cyclopropylmethyl)amino)cyclopropyl)pheny)bipheny-4-carbox amide hydrochloride (T-711) and 3-((1 S ,2 R )-2-(cyclobutylamino)cyclopropyl)- N -(5-methyl-1,3,4-thiadiazol-2-yl)benzamide fumarate (T-448)] revealed that T-711 modulates both of these functions and causes thrombocytopenia, while T-448 selectively inhibits histone demethylation with low hematological toxicity ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration is the pharmacokinetic (PK) properties of currently available LSD1 inhibitors, which have recently been shown to be ineffective against intracranial medulloblastoma despite very potent in vitro activity 35 . Two separate groups in Japan recently described new catalytic LSD1 inhibitors with favorable PK properties for potential use in neuro-oncology 36,37 . The transcription factor GFI1B is not disrupted by their compounds, reducing peripheral toxicity and sparing immune cells that would be critical for our combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…KDM1A is a histone demethylase that has been proposed as a target for the treatment of neurodegenerative or neurodevelopmental diseases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%